Photo-Thermal Superhydrophobic Sponge for Highly Efficient Anti-Icing and De-Icing - Yu, Bo (Langmuir : the ACS journal of surfaces and colloids, 2023)
Ice accretion always brings much inconvenience in the field of production and life. How to anti-ice or de-ice easily on solid surfaces becomes research focus in the engineering material fields. In this work, a kind of photo-thermal superhydrophobic polyurethane sponge (PSP-SPONGE) was developed by depositing Fe3O4 nanoparticles and polydopamine and simple fluorination treatment to realize anti-icing and de-icing fast under faint sunlight irradiation. Utilizing the thermal insulation of porous PSP-SPONGE, the photo-thermal energy was located at the sunlight irradiation area, which heated PSP-SPONGE surface rapidly under sunlight irradiation in cold surroundings. Water droplets on PSP-SPONGE surface would never freeze under faint 0.3 kW/m2 ("0.3 sun") sunlight illumination in -30 °C damp surroundings, and the ice melts entirely within 18 min under "1 sun" illumination. Furthermore, PSP-SPONGE has excellent self-cleaning and self-healing properties that can cope with the complex and volatile natural environment to guarantee durable anti-icing and de-icing performances. The simulated outdoor snow removal test also proved that snow on PSP-SPONGE surface could melt under "0.5 sun" sunlight illumination in -30 °C damp surroundings. The PSP-SPONGE fabricated with simple preparation and easy access has wide application prospects in anti-icing and de-icing